(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
This scientific article analyses the arguments and opinions used by the US Supreme Court and the Supreme Court of Brazil about air pollution control and the influence of transnational legal foundations in times of populist governments. For the development of this research, the comparative method was used, operationalized by the operational concept techniques, bibliographic research, and jurisprudential analysis. The product of the succinct comparative analysis performed allows us to classify the decision-making standard in the case of West Virginia v. EPA completely uncharted to foreigner law, while the Direct Action of Unconstitutionality n. 6.148/2019, constantly mentions transnational legal agreements and, in the case of regulatory omission by the Brazilian State, indicates the prevalence of World Health Organization standards.